Drug-drug interactions of ritonavir-boosted SARS-CoV-2 protease inhibitors in solid organ transplant recipients: experience from the initial use of lopinavir-ritonavir. (May 2023) - Gonzalez-García, Ruben; Roma, Joan-Ramon; Rodríguez-García, María; Arranz, Natalia; Ambrosioni, Juan; Bodro, Marta; Castel, Maria-Ángeles; Cofan, Federic; Crespo, Gonzalo; Diekmann, Fritz; Farrero, Marta; Forner, Alejandro; et al.
Abstract: Objectives: To review the drug-drug interactions between tacrolimus and lopinavir/ritonavir in 23 patients who received solid organ transplant during the first wave of COVID-19 and to determine the efficacy as well as safety of prednisone monotherapy. Methods: Observational study performed between March and June 2020 in solid organ transplant recipients admitted with an established diagnosis of SARS-CoV-2 infection who received lopinavir/ritonavir (≥2 doses). Once lopinavir/ritonavir therapy was initiated, calcineurin inhibitor treatment was temporarily switched to prednisone monotherapy (15–20 mg/d) to avoid drug-drug interactions and toxicity. After lopinavir/ritonavir treatment completion, immunosuppressive treatment was restarted with reduced doses of prednisone-tacrolimus (target minimum blood concentration –C0 - approximately 5 ng/mL). Patients were observed for 3 months to confirm the absence of rejection. Results: The median time from discontinuation of tacrolimus to initiation of lopinavir/ritonavir was 14 hours (interquartile range [IQR], 12–15) and from discontinuation of lopinavir/ritonavir to resumption of tacrolimus 58 hours (IQR, 47–81). The duration of lopinavir/ritonavir treatment was 7 days (IQR, 5–7). Nine of the 21 (42.8%) patients on tacrolimus treatment had C0 above the cutoff point after lopinavir/ritonavir initiation, despite having been substituted with prednisone before lopinavir/ritonavir initiation. Three patients had very high concentrations (>40 ng/mL) and developed toxicity. No episodes of acute rejection were diagnosed. Discussion: We did not observe toxicity in patients for whom tacrolimus was discontinued 24 hours before starting lopinavir/ritonavir and reintroduced at half dose 48 to 72 hours after lopinavir/ritonavir discontinuation. Prednisone monotherapy during lopinavir/ritonavir therapy was safe with no episodes of acute rejection. Experience with lopinavir/ritonavir may be applicable to the use of nirmatrelvir/ritonavir, but larger multicentre studies are needed to confirm these findings.